2000
DOI: 10.1097/00003246-200006000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin in septic patients: Effects on cardiovascular and renal function and its relationship to proinflammatory cytokines

Abstract: In patients with severe sepsis, big-ET plasma levels are markedly increased, even above those of multiple trauma patients, in close relationship to IL-6 and IL-8, and with significant correlation to renal function and pulmonary vascular tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 35 publications
3
41
0
3
Order By: Relevance
“…It is synthesized as a much longer polypeptide preproendothelin, being 203 amino acid residues long. Preproendothelin is cleaved by a signal peptidase to pro-ET-1, which in turn is cleaved by ET-converting enzyme (ECE) to the 21 amino acid long ET-1 (Brauner et al 2000;Hemsen et al 1996;Kido et al 1998;Schuetz et al 2011;Schweizer et al 1997;Tschaikowsky et al 2000). Using a sandwich immunoassay, Schuetz and colleagues evaluated proET-1 levels in patients with community-acquired pneumonia (CAP) and found that proET-1 levels at admission were independent predictors of short-term mortality and the need for ICU admission.…”
Section: Et-1 and Its Precursor Peptide Proet-1mentioning
confidence: 99%
“…It is synthesized as a much longer polypeptide preproendothelin, being 203 amino acid residues long. Preproendothelin is cleaved by a signal peptidase to pro-ET-1, which in turn is cleaved by ET-converting enzyme (ECE) to the 21 amino acid long ET-1 (Brauner et al 2000;Hemsen et al 1996;Kido et al 1998;Schuetz et al 2011;Schweizer et al 1997;Tschaikowsky et al 2000). Using a sandwich immunoassay, Schuetz and colleagues evaluated proET-1 levels in patients with community-acquired pneumonia (CAP) and found that proET-1 levels at admission were independent predictors of short-term mortality and the need for ICU admission.…”
Section: Et-1 and Its Precursor Peptide Proet-1mentioning
confidence: 99%
“…Circulating levels of endothelium-derived peptides such as adrenomedullin and endothelin are increased in response to infection and sepsis (12,31). These peptides are important mediators of vascular tone regulation: endothelin is a powerful vasoconstrictor, whereas adrenomedullin induces extreme vasodilatation and hypotension (11).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a direct association between infections and BNP is supported by evidence from preclinical studies, since LPS and pro-inflammatory cytokines have a direct effect on BNP transcription and translation in cardiomyocytes in vitro (15,30). Infection and sepsis also modulate circulating levels of other vasoactive peptides originating from the cardiovascular system, such as endothelium-derived endothelin-1 (ET-1) and adrenomedullin (12,31), as well as their corresponding prohormone fragments C-terminal pro-endothelin-1 (CT-proET-1) and midregional pro-adrenomedullin (MRproADM) (25,28).…”
mentioning
confidence: 99%
“…Endotoksemilerde ön-cül proteini olan prepro-ET-1, özellikle kalp ve akciğerlerden salınmaktadır ve mortalite hızlarıyla bağıntılı olarak artış göstermektedir (55,56). Yinelenen pro-ET-1 ölçümlerinin, özellikle toplum kökenli infeksiyonlarda CRP düzeyi ve löko-sit sayısına göre daha yüksek negatif prediktif değeri olduğu gösterilmiştir (57,58).…”
Section: Endotelin-1unclassified